Substâncias tóxicas persistentes (STP) no Brasil - Almeida, Fernanda V.; Centeno, Alberto J.; Bisinoti, Márcia Cristina [UNESP]; Jardim, Wilson F. (Sociedade Brasileira de Química, 2007)
The present article presents an assessment of PTS in Brazil including polychlorinated biphenyls, polycyclic aromatic hydrocarbons, benzene hexachloride, aldrin, dieldrin, endrin, p,p,-DDT, p,p,DDE, p,p,-DDD, hexachlorocyclohexanes (alpha-HCH, beta-HCH, gamma-HCH and delta-HCH), endossulfan, heptachlor and pentachlorophenol. The data presented here are related to a survey of PTS levels in different environmental matrixes (soil, sediment, water, air, biota) and human tissues (milk, blood, human hair), according to the scope of the UNEP-GEF Regionally Based Assessment of PTSs. Potential sources were evaluated considering national products and imports, since most of the literature does not allow source identification. Finally, Brazilian legislation was updated.
Persistent toxic substance (PTS) in Brazil
Keywords: persistent toxic substances; hotspots; environmental concentrations